2015
DOI: 10.1007/978-3-319-24264-4_8
|View full text |Cite
|
Sign up to set email alerts
|

An Ant Colony-Based Matheuristic Approach for Solving a Class of Vehicle Routing Problems

Abstract: Abstract. We propose a matheuristic approach to solve several types of vehicle routing problems (VRP). In the VRP, a fleet of capacitated vehicles visits a set of customers exactly once to satisfy their demands while obeying problem specific characteristics and constraints such as homogeneous or heterogeneous fleet, customer service time windows, single or multiple depots. The proposed matheuristic is based on an ant colony optimization (ACO) algorithm which constructs good feasible solutions. The routes obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The use of SPP as a postoptimization technique is reported in (Mancini, 2017;Gschwind and Drexl, 2019). The hybridization with heuristics is reported in many papers including (Prescott-Gagnon et al, 2009;Groër et al, 2011;Mendoza and Villegas, 2013;Subramanian et al, 2013;Parragh and Schmid, 2013;Yıldırım and Çatay, 2015;Grangier et al, 2017;Tellez et al, 2018;Dumez et al, 2021).…”
Section: Lns-spp Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of SPP as a postoptimization technique is reported in (Mancini, 2017;Gschwind and Drexl, 2019). The hybridization with heuristics is reported in many papers including (Prescott-Gagnon et al, 2009;Groër et al, 2011;Mendoza and Villegas, 2013;Subramanian et al, 2013;Parragh and Schmid, 2013;Yıldırım and Çatay, 2015;Grangier et al, 2017;Tellez et al, 2018;Dumez et al, 2021).…”
Section: Lns-spp Algorithmmentioning
confidence: 99%
“…The solution obtained is repaired if a customer is served more than once. Yıldırım and Çatay (2015) showed that solving an SCP instead of an SPP slightly shortens solving time. Additionally, an exact reparation is rarely needed and a greedy procedure generally finds the optimal reparation.…”
Section: Detail Of the Lns-spp Algorithmmentioning
confidence: 99%